PENYAKIT Kardiovaskular pada wanita : buku saku klinis / Kevin A. Bybee...[et al] ; alih bahasa, Rulli P.A. Situmorang ; editor, Sally Carolina, Rina Astikawati - Bybee, Kevin A.; Situmorang, Rulli P.A.; Sally Carolina; Rina Astikawati (Erlangga, 2014)
xvi, 198 hlm. : ilus. ; 16 cm